2022
DOI: 10.1038/s41524-022-00729-3
|View full text |Cite
|
Sign up to set email alerts
|

Distributed representations of atoms and materials for machine learning

Abstract: The use of machine learning is becoming increasingly common in computational materials science. To build effective models of the chemistry of materials, useful machine-based representations of atoms and their compounds are required. We derive distributed representations of compounds from their chemical formulas only, via pooling operations of distributed representations of atoms. These compound representations are evaluated on ten different tasks, such as the prediction of formation energy and band gap, and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…As a result, the symmetry‐related E g prediction was deteriorated but the E f and E h prediction quality never changed. Antunes et al [ 59 ] very recently revealed that it was successful to predict various material properties from chemical formulas only by employing brilliant atomic representations (e.g., SkipAtom, Atom2Vec, Bag‐of‐Atom, etc.). Nonetheless, we found that the XRD plays a significant role for the symmetry‐related E g prediction in the present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the symmetry‐related E g prediction was deteriorated but the E f and E h prediction quality never changed. Antunes et al [ 59 ] very recently revealed that it was successful to predict various material properties from chemical formulas only by employing brilliant atomic representations (e.g., SkipAtom, Atom2Vec, Bag‐of‐Atom, etc.). Nonetheless, we found that the XRD plays a significant role for the symmetry‐related E g prediction in the present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…A range of atomistic ML models has been introduced in recent years. The focus has mainly been on the regression of atom-resolved properties, or global properties as dependent on individual atomic environments . The construction of structural descriptors is often guided by physical ideas, encoding information about environments and symmetries, but this is not an indispensable practice, as complex neural networks have also been used to capture materials structures from raw data inputs.…”
Section: Intrinsically Interpretable Modelsmentioning
confidence: 99%
“…For all CraTENet and CrabNet models, the input, X in , consisted of n = 8 elements, and was zero-padded if the composition consisted of less than eight elements. Each element in the input was described with a SkipAtom distributed representation [108] with dimensions d in = 200. (We performed experiments, as described in supplementary note 1 and supplementary table 3, to determine the performance of different descriptors).…”
Section: Model Training and Evaluationmentioning
confidence: 99%